2010
DOI: 10.1007/s10811-010-9590-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and irradiance on photosynthesis and growth of a green-tide-forming species (Ulva linza) in the Yellow Sea

Abstract: Samples of the massive drifting green alga, Ulva linza, were collected from the coastal waters of the Yellow Sea, southwest of Korea, in early July 2009, and cultured under laboratory conditions. The effects of various temperature (10-30°C) and irradiance levels (0-1,000 μmol photons m −2 s −1 ) on photosynthesis, growth, and tissue nutrient content of U. linza were investigated in laboratory for both individuals of the latestage vegetation (LSV) and the early-stage vegetation (ESV). After 1 h acclimation to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 39 publications
0
40
1
1
Order By: Relevance
“…(Choi et al 2010). The same phenomenon occurred in the southwest sea of Korea (the southeastern part of the YS) in 2009, and the green mats were senescent with reduced physiological activity (Kim et al 2011). The green tide reoccurred in the southwest sea of Korea in July 2011, and off the coasts of China (the western part of the YS), and this has become an annual event in the YS.…”
Section: Methodsmentioning
confidence: 85%
“…(Choi et al 2010). The same phenomenon occurred in the southwest sea of Korea (the southeastern part of the YS) in 2009, and the green mats were senescent with reduced physiological activity (Kim et al 2011). The green tide reoccurred in the southwest sea of Korea in July 2011, and off the coasts of China (the western part of the YS), and this has become an annual event in the YS.…”
Section: Methodsmentioning
confidence: 85%
“…And the morphological characteristics displayed continuously through several generations cultured in the laboratory (Hiraoka et al, 2011). What is more, living conditions, such as the temperature range , irradiance (Kim et al, 2011), desiccation and salinity (Wei et al, 2010), are obviously different between the littoral attached and the floating populations in the Yellow Sea. Compared to the attached populations, the floating population was better adapted to the habitat on the sea surface (Hiraoka et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, limited reproduction and sinking may be more common in the middle of the Yellow Sea because of the significantly lower amounts of nutrients (Wang et al, 2003). Kim et al (2011) reported that green algal mats observed in the southeastern Yellow Sea in 2009…”
Section: Discussionmentioning
confidence: 99%
“…Green tides appeared along the southwestern shore of Korea and around Jeju Island in Korea in 2008(Choi et al, 2010, 2009 (Kim et al, 2011), 2011 (Son et al, 2012;Son et al, 2015(MBC News, 2013. As for studies on floating green algae found in Korean waters, Choi et al (2010) identified green tide near Jeju Island during a field study in 2008.…”
Section: Introductionmentioning
confidence: 99%